IMPLEMENTASI SISTEM PEMBUKUAN DIGITAL DALAM MENDUKUNG TRANSFORMASI PENGELOLAAN KEUANGAN UMKM (STUDI KASUS: KOLEGA BARBERSHOP, CIKARANG SELATAN) - Fera Lufhidarani Pranita; Apri Maulana (POLITEKNIK LP3I JAKARTA, 2025)
Financial reports play a crucial role in assisting and monitoring the financial condition of various parties involved in a business's financial performance. They provide information on account structure, transaction recording, and the preparation of financial reports that provide quantitative information on the financial position and changes occurring at the Kolega Barbershop MSME using Microsoft Excel. This study employed a qualitative method with a descriptive approach. Data collection techniques included a literature review using scientific sources, as well as field studies involving observation, interviews, and documentation of financial recording activities at Kolega Barbershop. The results indicate that the financial recording process at Kolega Barbershop is still manual, resulting in incomplete and unsystematic financial reporting. This potentially leads to recording errors. It can be concluded that the preparation of financial reports does not comply with applicable accounting standards, requiring special training for business owners to improve their ability to record and prepare more accurate and efficient financial reports.